A mean field model of agglomeration as an extension to existing precipitation models. (15th June 2020) - Seret, Anthony; Moussa, Charbel; Bernacki, Marc; Bozzolo, Nathalie
Graphical abstract: Abstract: This work presents an analytical mean field model of agglomeration (equivalent agglomeration model, EAM) by contact between growing precipitates. The principle of the EAM is to add a 2-steps task to existing precipitation models: at each time-step, (1) calculate the number of agglomerations per unit volume, then (2) use it to update the numbers and radii of classes in order to take agglomeration into account. The first step is validated by full-field simulations of growing spheres randomly placed in a cube. The EAM can be added as extension to existing precipitation models and be applied to the mean radius, multi-class Lagrangian and multi-class Eulerian representations of the precipitate population. The EAM is incorporated to a mean field precipitation model based on the classical nucleation theory and Zener's law for size evolution, and catches the rarefaction of γ ″ precipitates agglomerating as they grow during an isothermal annealing in a nickel-based superalloy.